Prototype of blood sugar measuring instrument with non invasive method using near infrared - Saraswati, Irma; Dzaky, Muhammad Fikri; Haryanto, Heri (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
At present the measurement of blood sugar still uses an invasive tool, this disrupts the patient's comfort and can cause infection and pain. So that a non-invasive tool is needed to measure blood sugar. Tool testing was done by measuring blood sugar levels in 35 patients and seeing a correlation between the value of blood sugar levels with ADC. The test results showed that the value of changes in blood sugar levels followed y = -0.146x + 164.89 Coefficient value R = 0.9233 The value of the accuracy of the tool was 91.086% and the precision of 94.3026%. Blood sugar measuring devices that have been designed to monitor the blood sugar of users by using the internet. This blood sugar meter cannot be used as a reference for the actual blood sugar level. However, the realization of this tool can still determine a rough estimate of the high and low levels of sugar in the blood.